Estrategias de escarificación para eliminar la latencia en semillas de Cenchrus ciliaris L. y Brachiaria brizantha cv. Marandu - Martínez Sánchez, Jesús; Villegas Aparicio, Yuri; Enríquez-del Valle, José Raymundo; Carrillo Rodríguez, José Cruz; Vásquez Dávila, Marco Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to eliminate dormancy and improve seed germination of Cenchrus ciliaris L. and Brachiaria brizantha cv. Marandu, was determined the effect of treatments: a) physical: seed immersion during different times 12, 24 and 48 h in water with constant circulation; b) Chemicals: immersion during different times 2 and 4 min in H2SO4 diluted at 50% and for 2 h in KNO3 0.5%; c) mechanical: removal of glumes; and d) a control without treatment. The experiment was established under laboratory conditions according to a completely randomized design with an incomplete factorial array 2 x 8, where the factors were the two species and the eight seed treatments. In the case of Brachiaria brizantha cv. Marandu seeds did not had treatment with accessory structures. The experimental unit consisted of 50 seeds and had four replicates, in which were evaluated the percentage and speed of germination. In seed s of Brachiaria brizantha cv. Marandu subjected to immersion during four minutes immersion in H2SO4 diluted at 50%; 34% of these germinated at a germination speed of 2.71 plants day-1 values significantly higher compared to other treatments. The seeds of Cenchrus ciliaris L. subject to the treatment of glumes removal were the only group of seeds of this species where germination occurred (12.5%).
Keywords: sulfuric acid; germination; glumes; pastures